Matriz de riscos nos contratos de concessões rodoviárias - Santos, Alexandre Silva (2022)
The public service of national infrastructure, from the mid-1990s, began to be provided jointly to the private sector through contracts through the bidding law. From 1995 onwards, with the enactment of the concession law, the State sought private partners to carry out these services, assuming all the risk of the enterprise and public works within a certain period. The objective of this research is to identify and compare the allocation of contractual risks in a risk matrix in the Federal and Paulista Highway Concessions from 2009 to 2020. This research investigated 16 concession contracts, 8 federal and 8 state, corresponding to the period from 2009 to 2020. 2020, with textual analysis of risk allocations between the Grantor and Concessionaire, in order to describe relationships of differences and similarities between contracts. During these periods, the dimensions of the highways, contracted values, economics and political aspects of the federal and state governments were disregarded. Contracts were consulted by the portals of the federal and state transport regulatory agencies, and the contractual clauses were listed in the construction of a risk matrix that was paired and compared by reading and analyzing the convergences and divergences regarding the normative isomorphic aspect and based on the differentiation of the highways in the State of São Paulo due to the quality of its highways, which is among the 10 best in the country. The results found are a convergence of 57% of the contractual clauses, with occasional divergences in the amount of 19% in federal contracts with exclusive clauses; and 17% in the states. It was observed that the contracts seek a trend in relation to contracts in São Paulo, but some aspects diverge in relation to the quality of services. The contribution of this research lies in the practical application of the concepts of the new public governance such as: networking, new actors, accountability, accountability, transparency and accountability. More specifically, the risk matrix as a management tool can contribute to the effective use of resources, mapping contractual risks. This research highlights the convergences in the observation of risks of contracts drawn up by the federation and the State of São Paulo, allowing other entities of the federation to evaluate them in similar contracts.